2020
DOI: 10.1136/medhum-2019-011751
|View full text |Cite
|
Sign up to set email alerts
|

Towards a translational medical humanities: introducing the cultural crossings of care

Abstract: In this introductory essay, we will present a translational medical humanities approach where the humanities are not only an auxiliary to medical science and practice, but also an interdisciplinary space where both medicine and the humanities mutually challenge and inform each other. First, we explore how medicine’s attempt to tackle the nature–culture divide is emblematically expressed in the concept and practice of knowledge translation (hereinafter KT). Second, we compare and contrast KT as an epist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…3 We argue that translation, "no longer deemed a mere instrument of international relations, business, education, and culture" (Apter 2006, 3), plays a key role in the understanding of the epidemiology of diseases, as it helps us explore concepts of infectivity and immunity in terms of cultural and biological resistance. In line with second-wave medical humanities (Whitehead et al 2017), we urge the adoption of a translational medical humanities framework to evaluate better the mechanisms of biocultural contagion, with science understood as the manifestation of (one, hegemonic) culture rather than the infallible repository of truth (Engebretsen, Henrichsen, and Ødemark 2020). We hope that these initial operations will lay the foundations, on the one hand, for a more capacious understanding of translational medicine that incorporates perspectives from the humanities (especially translation studies) and, on the other, for a paradigmatic shift in translation studies itself as the discipline's epidemiological implications begin to be revealed.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…3 We argue that translation, "no longer deemed a mere instrument of international relations, business, education, and culture" (Apter 2006, 3), plays a key role in the understanding of the epidemiology of diseases, as it helps us explore concepts of infectivity and immunity in terms of cultural and biological resistance. In line with second-wave medical humanities (Whitehead et al 2017), we urge the adoption of a translational medical humanities framework to evaluate better the mechanisms of biocultural contagion, with science understood as the manifestation of (one, hegemonic) culture rather than the infallible repository of truth (Engebretsen, Henrichsen, and Ødemark 2020). We hope that these initial operations will lay the foundations, on the one hand, for a more capacious understanding of translational medicine that incorporates perspectives from the humanities (especially translation studies) and, on the other, for a paradigmatic shift in translation studies itself as the discipline's epidemiological implications begin to be revealed.…”
Section: Introductionmentioning
confidence: 94%
“…Even though such a definition of translation may be deemed contradictory-translation being at once disease-causing and disease-stopping-it is in fact justified by translation's very nature, which is paradoxical by definition. As it functions through and permits the coexistence of opposites-science and culture (Engebretsen, Henrichsen, and Ødemark 2020), dominance and marginality (Venuti 1995), uniqueness and multitude (Reynolds 2020), to give just a few examples-translation positions itself at the intersection of different disciplinary and cultural boundaries, be they professional, spatial, temporal, or linguistic. Ultimately, translation contaminates the supposed purity of an original (scientific) object, multiplies the singular, and stages the unseen workings of transmission, thus enacting a pandemic-like experience.…”
Section: Theorizing the Translation-contagion Nexus: Rules And Curesmentioning
confidence: 99%
“…Beneath more radical approaches that call for a new form of epistemology in medicine, such as the ‘situated epistemology’ approach, 19‐21 the post‐normal science concept, 22,23 or the integration and implementation science concept 24,25 and other approaches, 26 there are at least two ‘softer’ approaches currently discussed to prepare EbM for future challenges: (1) the organic turn approach 1 and (2) the EbM+ approach 27‐30 . Within the first approach, many scholars and institutions of EbM have delivered solutions to adapt EbM to a fast‐changing world, mainly by accelerating the evidence‐producing and ‐reviewing process by making the EbM process less formal and more agile (e.g., rapid reviews and living guidelines) and accepting mathematical modelling as another method for gaining knowledge 2,31‐36 .…”
Section: Ebm+theory: Integrating Empirical and Theoretical Evidencementioning
confidence: 99%
“…It has proven useful to thinkers as diverse as Martin Heidegger, Arthur Kleinman ( Kleinman and van der Geest 2009 ) and Julia Kristeva ( Kristeva (2012) , Kristeva et al 2018 ). While utilisation by Heidegger 1927, 196–200 ‘challenges the myth of self-sufficiency and individual atomization that that has shaped much of modern Western philosophy’ ( Froese 2005, 16 ), both Kleinman and Kristeva explore the tension between universalised knowledge and the singularity of individual patients and intimate care ( Engebretsen, Fraas Henrichsen, and Ødemark 2020 ).…”
Section: Introductionmentioning
confidence: 99%